Regulatory control for herbal and traditional medicines in Malaysia: issues and challenges - Ismail, Suzi Fadhilah; Abdul Ghani Azmi, Ida Madieha; Daud, Mahyuddin; Abd. Jalil, Juriah; Safuan, Sahida (2018)
Many herbs are believed to be beneficial in curing diseases, in addition to improving general health and well-being. With the booming of many herbal and traditional medicines in local markets, it is feared that the harmful side effects might prevail over their potential benefits as there is a lack of or even no scientific basis for the belief. These categories of medicines generally fall under the purview of various regulations such as the Poison Act of 1952, Sale of Drug Act of 1952, Advertisement and Sale Act of 1956, and the Control of Drugs and Cosmetics Regulations of 1984. Despite these regulations, production and sale of traditional medicines might pose some issues in relation to their safety to the consumers as they contain some new active ingredients of plant extracts which are chemicals that have the potential of causing adverse implication to health, similar to those purified medications. Many of these products are registered as food supplements or vitamins, of which registration requirements are much less stringent than that classified as pharmaceutical products. Setting on this background, this paper seeks to examine current legal framework regulating herbal and traditional medicines in Malaysia, with a special emphasis on the issues and challenges revolving around them. Relevant laws from selected jurisdictions such as United Kingdom, European Union,Australia and Japan will also be highlighted with the aim of emulating the suitable, best practice from these countries. This paper concludes with some suggestions to overcome the problems and weaknesses of the current legal mechanism in regulating products of herbal and traditional medicines.